(untitled) (Archives of Mechanics - Test, 2002)
Basic inequalities for diagonal and subdiagonal multipoint Padé approximants to N power series expansions of Stieltjes function f0 at points x1, x2,..., xN are derived. For particular cases the inequalities obtained reduce to those obtained earlier for one-, two- and three-point Padé approximants in [1], [5] and [23], respectively. Numerical examples illustrating the relations achieved are also provided. Our results can be applied to the determination of bounds on the effective moduli of bone subjected to torsion and composites in the case of transport equations.